Acoustic analyses using MATLAB and ANSYS - Howard, Carl Q., 1970-; Cazzolato, Benjamin S., 1969- (CRC Press, 2015)
"This book describes the use of Ansys finite element analysis software and MATLAB® to solve acoustic problems. These range from simple textbook problems, to complex ones that can only be solved using FEA software. The book includes instructions on relevant mathematical modelling, and hints on the use of Ansys software. The MATLAB source code provides readers with valuable tools for doing their own validations, and is available for download. The book provides practical training in the use of FEA for basic modelling and solving acoustic problems"--